1995
DOI: 10.1080/07448481.1995.9937507
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries in a College-Age Population During a 1-Semester Term

Abstract: The authors' retrospective survey assessed the incidence and causes of sport- and exercise-related injuries in college students participating in intramural, recreational, and club sports. For their survey, they examined clinical screening forms and medical charts of 300 students (160 men and 140 women) to determine the type of injury, the body part affected, loading behavior of tissues involved, and mechanism of the injuries. Sprains resulting from tensile forces accounted for most of the injuries, with the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding the different type or cause of nonfatal injury in university students, this study found, in agreement with other studies (Sane et al., ; Shi et al., ; Sumilo & Stewart‐Brown, ) that most students had sustained their injuries during sports activities and that the most common causes were falling and traffic‐related injuries. This study finding calls for a need for programs in sport‐injury prevention for university students (Donaldson & Finch, ; Zebas, Loudon, Chapman, Magee, & Bowman, ). In particular, injuries caused by animal bites were found to be high (6.2% among injured) among university students from participating Southeast Asian countries.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the different type or cause of nonfatal injury in university students, this study found, in agreement with other studies (Sane et al., ; Shi et al., ; Sumilo & Stewart‐Brown, ) that most students had sustained their injuries during sports activities and that the most common causes were falling and traffic‐related injuries. This study finding calls for a need for programs in sport‐injury prevention for university students (Donaldson & Finch, ; Zebas, Loudon, Chapman, Magee, & Bowman, ). In particular, injuries caused by animal bites were found to be high (6.2% among injured) among university students from participating Southeast Asian countries.…”
Section: Discussionmentioning
confidence: 91%